2016
DOI: 10.1111/1471-0307.12318
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and microbial properties of nanopowdered peanut sprout‐supplemented Caciocavallo‐like cheese during ripening

Abstract: This study was carried out to investigate the physicochemical and microbial properties of nanopowdered peanut sprout‐supplemented Caciocavallo‐like cheese (NPSCC) during ripening at 14 °C for 6 weeks. The total phenol contents and lactic acid bacteria counts in NPSCC were significantly higher than those in the control, indicating that nanopowdered peanut sprout could potentially be used as a prebiotic and potential source of dietary antioxidants in the dairy products. Thiobarbituric acid values of the cheese w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…LAB counts of the microcapsule-treated cheeses were significantly higher compared to controls as the ripening period proceeded from 0 to 60 d ( p <0.05). Similarly, in Queso Blanco, Caciocavallo, and Mozzarella cheeses, the LAB counts increased during ripening ( Bermudez-Aguirre and Barbosa-Canovas, 2012 ; Ko et al , 2017 ; Van Hekken et al , 2012 ). Increasing the concentrations of powdered microcapsules containing tomato extracts proportionally decreased the LAB counts in Queso Blanco cheeses because of the antibacterial activity of lycopene ( Bartkiene et al , 2015 ; Mukhopadhyay et al , 2014 ).…”
Section: Resultsmentioning
confidence: 81%
“…LAB counts of the microcapsule-treated cheeses were significantly higher compared to controls as the ripening period proceeded from 0 to 60 d ( p <0.05). Similarly, in Queso Blanco, Caciocavallo, and Mozzarella cheeses, the LAB counts increased during ripening ( Bermudez-Aguirre and Barbosa-Canovas, 2012 ; Ko et al , 2017 ; Van Hekken et al , 2012 ). Increasing the concentrations of powdered microcapsules containing tomato extracts proportionally decreased the LAB counts in Queso Blanco cheeses because of the antibacterial activity of lycopene ( Bartkiene et al , 2015 ; Mukhopadhyay et al , 2014 ).…”
Section: Resultsmentioning
confidence: 81%
“…Due to size reduction, the bioavailability of the nutrients in red ginseng was considered to be increased. Similarly, Ko () also reported that the addition of nanopowdered peanut sprout in Caciocavallo cheese nourished the growth of LAB. In conclusion, the addition of red ginseng promoted the growth of LAB; NRG showed more efficacies in increasing LAB than PRG, but the difference was not significant.…”
Section: Resultsmentioning
confidence: 84%
“…). Ko () investigated the incorporation of nanopowdered peanut sprout into caciocavallo cheese to promote the functionality of the cheese. The result of this study showed that the quantity of resveratrol, which is the major polyphenol, in the cheese increased during ripening.…”
Section: Introductionmentioning
confidence: 99%
“…Cheeses with addition of peanuts have been developed through nanoencapsulation. For example, Ko et al (2017) used nanopowdered peanut sprout to fortify Caciocavallo cheese. The powder particles had a diameter between 73 and 640 nm with an average particle size of 300-350 nm.…”
Section: Cheese Fortification By Direct Incorporation Of Oils and Oilmentioning
confidence: 99%